Protective antioxidative and anti-inflammatory actions of β-caryophyllene against sulfasalazine-induced nephrotoxicity in rat. Issue 8 (April 2022) - Refaat, Bassem; El-Boshy, Mohamed
The pathogenesis of sulfasalazine (SFZ)-induced nephrotoxicity is unclear. Moreover, there are no reports on the protective effects of β-caryophyllene (BCP) against SFZ-induced renal injury. Hence, in this study, we measured several oxidative stress and inflammatory regulatory molecules alongside the effects of BCP in SFZ-intoxicated rats. Male rats ( n = 48) were distributed to six equal groups as follows: negative control (NC), normal rats treated with low (N-LD; 200 mg/kg/day) and high (N-HD; 400 mg/kg/day) BCP doses, and animals treated with SFZ individually (PC; 600 mg/kg/day) or combined with BCP low (P-LD) and high (P-HD) doses. All drugs were administrated for 14 consecutive days. The NC, N-LD, and N-HD groups showed comparable renal histology and biochemistry. In contrast, abnormal histology, and increased creatinine and urea alongside oliguria and proteinuria were detected in the PC group. Renal specimens from the PC group revealed increased levels of nuclear factor-kappa B (NF-κB), transforming growth factor (TGF)-β with kidney injury molecule (KIM)-1, while the levels of nuclear factor erythroid 2-related factor 2 (Nrf2), AMP-activated protein kinase (AMPK), and protein kinase B (AKT) declined, relative to controls. The PC renal tissue also had markedly higher levels of inflammatory cytokines (tumor necrosis factor [TNF]-α/interleukin [IL]-1β/IL-6) and pro-oxidants (malondialdehyde [MDA]/H2 O2 /protein carbonyls), whereas those of antioxidants (glutathione [GSH]/glutathione peroxidase [GPx]/superoxide dismutase-1 [SOD1]/catalase [CAT]) and IL-10 decreased and were associated with marked apoptosis. Both BCP regimens ameliorated renal functions and histology, and reduced NF-κB, TGF-β, and KIM-1 levels in addition to those of oxidative stress and inflammation markers. Both protocols also augmented Nrf2, AMPK, AKT, antioxidants, and IL-10. However, P-HD showed better alleviating effects than the N-HD group. In conclusion, this study is the first to link NF-κB, TGF-β, Nrf2, AMPK, and AKT with SFZ-induced nephrotoxicity. In addition, this is the first report to reveal antioxidative and anti-inflammatory effects for BCP against SFZ-associated nephropathy.